Determinants of research productivity and efficiency among the Arab world’s accredited business schools - Dima Jamali (9700306) (2023)
This article presents a bibliometric analysis of the research output of the Arab world’s 30 AACSB- and EQUIS-accredited business schools between 2013 and 2022. The analysis aims to provide an overview of the research performance of these schools, identify research strengths, and highlight areas for improvement. The study examines 12,693 publications indexed in the Scopus database. The findings reveal remarkable progress in research productivity, including a steady increase in publications in high-impact journals. Notably, business schools in Lebanon, Oman, Qatar, and the United Arab Emirates demonstrate exceptional research performance. The study also reveals variations in citation impact based on publication type, co-authorship patterns, international collaborations, journal rankings, and disciplines. The research themes explored by the Arab world’s accredited business schools cover a wide variety of topics, including personnel, innovation, trade openness, mobile banking/payment, stock and financial markets, economic growth, supply chain, corporate social responsibility, entrepreneurship, community participation, and oil prices and markets, among others. The research areas align with several United Nations sustainable development goals. These findings offer valuable insights for the region’s business schools to benchmark their research performance and gain a nuanced understanding of the factors that contribute to increased research productivity and impact. The study concludes that business schools in the Arab region must continue to enhance their publication rates in top-tier journals, foster improved international collaborations, and implement new research incentive schemes and excellence initiatives that recognize and reward high-quality research. Other Information Published in: Management Review Quarterly License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11301-023-00365-1